Access to needle and syringe programs and the relationship to equipment sharing among people who inject drugs in Kermanshah, Iran - Rezaie, F.; Farhadi, M.; Farhoudian, A.; Najafi, M.; Bazrafshan, A.; Higgs, Peter; Mohammadi Shahboulagh, F.; Ranjbar, M.; Vameghi, M.; Abbasi, M.; Noroozi, A.; Noroozi, M. (Informa Healthcare, 2017)
© 2017 Taylor & Francis Group, LLC. Background: Needle and Syringe Programs (NSP) have been implemented in Iran since 2002. The primary aim of NSP is to prevent blood-borne virus transmission by providing sterile injecting equipment and information on safer injection practices. However, while NSP has been implemented in Iran for more than a decade, only a limited number of studies have evaluated the effect access to NSP has in reducing risk behaviors among people who inject drugs (PWIDs).Methods: Between September and December 2014 we used snow ball sampling to recruit PWID from Kermanshah for a cross-sectional survey. Participants completed a face-to-face interview and provided information on the frequency of injection and drug-related risk behaviors such as sharing (borrowing or lending) of previously used syringes/needles and the number of injecting partners with whom they have shared syringes/needles in the two months prior to interview. Correlation between drug-related risk behaviors and ability to access NSPs was assessed by bivariate and multiple logistic regression through the estimation of odds ratios (OR) and 95% confidence intervals (95% CI).Results: Of 500 PWIDs in this study, 18%, 36% and 46% reported low, medium and high ability to access NSPs in the two months prior to interview, respectively. The odds of receptive syringe sharing among people with low-access was 3.5 times the odds of people with high-access when adjusted for covariates and remained statistically significant (adjusted odds ratio (AOR): 3.5, 95%CI 1.4–7.7). The relationship between access to NSP and use of sterile-injecting equipment was not statistically significant. The AOR for outcomes like paraphernalia sharing (AOR: 2.5, 95%CI: 0.6–4.6, p-value: 0.6) was not statistically significant.Conclusions: Similar to the previous research in international settings, this study found that PWID who reported to have more access to needle and syringe programs were less likely to use a syringe after someone else had used it. NSP program staff should focus on encouraging more frequent visits, increasing the opening hours and number of locations providing access to sterile syringe in settings with high concentrations of PWID.